Analgesic nitrous oxide for alcohol withdrawal: a critical appraisal after 10 years' use. - Gillman, M. A. (BMJ Group, 1990)
We describe a method of treating the mild to moderate alcohol withdrawal state which has been used successfully for 10 years in over 7,000 cases. It is now the standard therapy at the largest dedicated alcoholic rehabilitation centre in Southern Africa. The technique uses analgesic (subanaesthetic) concentrations of nitrous oxide, which in most cases is administered on a single occasion for 20 minutes only. This results in the most rapid detoxification presently available, such that within an hour of the commencement of therapy the patient is so improved that they can eat the next ward meal. Provided the correct equipment and simple training is used this non-anaesthetic treatment is completely free of any serious side effects and the patient is at all times conscious and cooperative. Apart from this the amounts of sedative medication, such as benzodiazepines, are drastically reduced during detoxification. Because of the rapidity of the therapeutic response this technique is useful also as a screening test for assessing those patients requiring intensive therapy for the alcohol withdrawal state. There is evidence of the usefulness of analgesic nitrous oxide therapy for treating other addictive withdrawal states including opioid and nicotine.